2009
DOI: 10.1007/s00114-009-0586-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of Mediterranean chukar (Alectoris chukar, Galliformes) populations: conservation and management implications

Abstract: The chukar (Alectoris chukar, Galliformes) is a species hunted throughout its native range from the East Mediterranean to Manchuria and in the USA, which hosts the world's largest introduced population. This study aims to investigate the genetic structure of Mediterranean chukar populations to aid management decisions. We genotyped 143 specimens at two regions of the mitochondrial DNA (mtDNA: cytochrome b, control region) and eight loci of the microsatellite DNA. Samples were collected in northern (Limnos, Les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Piertney et al 2001;Segelbacher and Piertney 2007;Barbanera et al 2009). A recent study that quantified mitochondrial genetic diversity in choughs did not find any polymorphism in a 365 bp control region segment among 23 extant Welsh choughs and 19 museum specimens from across the British Isles, and concluded that all extant choughs in the UK form a single matrilineage (Kocijan and Bruford 2011).…”
Section: Genetic Diversitymentioning
confidence: 93%
“…Piertney et al 2001;Segelbacher and Piertney 2007;Barbanera et al 2009). A recent study that quantified mitochondrial genetic diversity in choughs did not find any polymorphism in a 365 bp control region segment among 23 extant Welsh choughs and 19 museum specimens from across the British Isles, and concluded that all extant choughs in the UK form a single matrilineage (Kocijan and Bruford 2011).…”
Section: Genetic Diversitymentioning
confidence: 93%
“…All simulations were run with 10 6 iterations, following a burn-in period of 10 5 iterations, and replicated four times per each Kvalue. We assumed that the maximum number of populations (K) varied between 1 and 8, and calculated the optimal K value and the identification threshold (Q i = 0.90; cf., Vaha and Primmer 2006) to assign each individual to one or jointly to two clusters as in Barbanera et al (2009b).…”
Section: Microsatellite Dnamentioning
confidence: 99%
“…We also used analogous STR profiles of genetically homogeneous A. rufa (n = 30, Spain) and A. chukar (n = 30: Greece, Cyprus) (Barbanera et al 2010) as reference to test the East Anglian RLP population for the occurrence of hybrids between the two species. PCR conditions were as in Barbanera et al (2009b).…”
Section: Microsatellite Dnamentioning
confidence: 99%
“…An alternative explanation is that there is a continuous influx of hybrid birds into wild populations because of repeated (annual) and massive (3-4 millions/year in Spain) releases of captive-bred birds, and because of a high prevalence of hybrids in farms, with poor or no genetic control (hybrids have been detected in c. 63% of farms used for releasing partridges; Blanco-Aguiar et al 2008). Thus, even although few released birds would survive in the wild, massive releases conducted over many years in the same area would allow hybrid partridges to be maintained in wild breeding populations (Barbanera et al 2009b). Summarizing, the lower survival rate of hybrids could limit their spread into wild populations in the long term, but our data do not allow a complete demographic evaluation, because this lower adult survival could be compensated by a higher productivity.…”
Section: Hybridizationmentioning
confidence: 95%